Apelin/APJ system: a novel promising target for anti-oxidative stress in stroke - Xu, Weilin; Yan, Jun; Travis, Zachary D.; Lenahan, Cameron; Gao, Liansheng; Wu, Haijian; Zheng, Jingwei; Zhang, Jianmin; Shao, Anwen; Yu, Jun (Frontiers in Pharmacology, 2025)
The apelin/APJ system has garnered increasing attention in recent years. In this review, we comprehensively discuss the physiological and pathological mechanisms of the apelin/APJ system in stroke. The apelin/APJ system is widely expressed in the central nervous system (CNS). However, the distribution of the apelin/APJ system varies across different regions and subcellular organelles of the brain. Additionally, the neuroprotective effects of the apelin/APJ system have been reported to inhibit oxidative and nitrative stresses via various signaling pathways. Despite this, the clinical application of the apelin/APJ system remains distant, as apelin has numerous active forms and signaling pathways. The development of a range of drugs targeting the apelin/APJ system holds promise for treating stroke.